THE EFFECTIVENESS OF TEAM ASSISTED INDIVIDUALIZATION (TAI) TOWARDS STUDENTSâ WRITING - Susilawati, Erni (Journal of Languages and Language Teaching, 2016)
This research was aimed to find out Â The Effectiveness of Team Assisted Individualization (TAI) is effective towards studentsâ writing. The research was quasi experimental research and the design that used was the pre-test and post-test design. The population of the study was the second grade students of SMPN 4 Praya Barat which consisted of two classes. Those classes were took as the samples, those were VIIIC as experimental class and VIIIA as control class. Experimental class was treated by using Team Assisted Individualizati0n (TAI) and control class was treated by using Roundtable technique. The instrument that was used essay test, the topic was about descriptive text. The score were analyzed by using descriptive and inferential analysis, descriptive analysis was used to describe mean, median, mode and standard deviation both of group, and the inferential analysis was used describe the value of t-test for comparison between t-table. Based on the analysis, it shows that the value of (t-test) was 2,95 is higher than the value of (t-table) was 1,688 as the level of significance level was 0,05 and the number of degree of freedom (df) was 36. Therefore, based on the result of the analysis, it be concluded that Team Assisted Individualization (TAI) was effective toward studentsâ writing. The results of this research showed that Team Assisted Individualization (TAI) was compatible in writing because the technique given many advantages, the studentsâ feel comfortable to learn in group and they were argued that Team Assisted Individualization (TAI) make the teaching learning process more interesting since they can ask and can be peer tutoring for their friends. Finally, the researcher suggests that in teaching writing the teacher should be creative in preparing and delivering writing materials.